Improvement of the Supercapacitor Performance of Nickel Molybdenum Chalcogenides/Reduced Graphene Oxide Composites through Vanadium-Doping Induced Crystal Strain Relaxation and Band Gap Modification - Ghosh, Souvik; Samanta, Prakas; Jang, Wooree; Yang, Cheol-Min; Murmu, Naresh Chandra; Kuila, Tapas (AMER CHEMICAL SOC, 2022)
Metal chalcogenide/reduced graphene oxide (RGO) composites have gained significant interest as promising electrode materials for supercapacitor application. Herein, the effect of different chalcogens (O, S, and Se) on nickel-based bimetallic composites along with the addition of a scanty amount of a heteroatom (V) is investigated. Different sizes and electronegativity of the chalcogens alter the morphology of the composites. However, V doping does not change the morphology but regulates the crystalline strain, band-gap energies, and charge transfer kinetics of the materials. All these factors are very important in controlling the performance of a supercapacitor device. Among all the doped and undoped composites, Se-based electrode materials exhibit the highest supercapacitor properties. In a three-electrode configuration, the V-doped Ni-Mo selenide/RGO (VNMSeR) composite electrode exhibits the highest specific capaci-tance of similar to 610 C g(-1) (1220 F g(-1)) at 2 A g(-1) current density with a superior rate capability of similar to 73.7%. An asymmetric supercapacitor device has been fabricated using VNMSeR as positive and thermally RGO as negative electrode. The device exhibits a maximum energy density of similar to 60.5 Wh kg(-1) at a power density of 1.47 kW kg(-1) and shows similar to 83.4% retention (50.5 Wh kg(-1)) in energy density when the power density increases by similar to 8.25-fold (12.12 kW kg(-1)).